PENGARUH PERBANDINGAN TERIGU DAN PASTA BROKOLI (Brassica oleraceae L.) TERHADAP KARAKTERISTIK DONAT - Shahrirputra, Adryan Adhitama; Ina, Putu Timur; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p11, 2019)
This research was conducted with the aims to determine the effect of wheat flour and broccoli paste to the characteristics of donut and obtain a ratio of wheat flour and broccoli paste which able to produce donut with the best characteristics. This research used randomized block design with the treatment of wheat flour and broccoli paste ratio 100 %:0%; 9 0%: 1 0%; 8 0%: 2 0%; 7 0%: 3 0%; 60%:40%. The treatment was repeated 3 times to obtain 15 units of experiment. The data were then analyzed by Analysis of Variance and if the treatment had an significant effect, the Duncan test were performed. The results showed that the ratio of wheat and broccoli paste had an significant effect on water content, fat content, crude fiber content, vitamin C content, chlorophyll content, swelling ability , flavor (hedonic), texture (scoring) of donut . Ratio of 60% wheat : 40% broccoli paste is the best donut characteristic with 18.80% water content, 17.30% fat content, 4.92% crude fiber content, 2.93 mg/g vitamin C content, 3.97 mg/kg chlorophyll content, 27.20% swelling ability , rather liked color, ordinary flavor, soft and rather liked texture, rather liked taste, and overall acceptance is rather liked. Keywords : wheat flour, broccoli paste, donut